(3QSGdI aj CaYd EPG cGf ddJaVjds ((3eMehO UObi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf EYde Cf dEaYd EPG cGf ddJaVjd KdGKI CMhGd GdChd Cf jchf eYg ef fMh RjO CaVd ef YeQh hGdKGfi Cf JONd Ydjg GdCda hGddGe s
(3BNQgG (B:s
(3hdG Tc Cf GdLejY ai Mce CaYd GdJaVjd hGddg CYde JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdfMhs